2009
DOI: 10.1007/s00534-009-0209-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hilar cholangiocarcinoma in the “new era”: the Nagoya University experience

Abstract: Objective To review our surgical experience with hilar cholangiocarcinoma in the “new era.” Methods The medical records of 428 patients with hilar cholangiocarcinoma who underwent treatment between 2001 and 2008 at the First Department of Surgery, the Nagoya University Hospital, were retrospectively reviewed. Results Of the 428 patients, 298 (70%) underwent surgical resection (R0,n = 220; R1,n = 70; R2,n = 8). Portal vein resection was performed in 111 (37%) patients, and hepatic artery resection was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(132 citation statements)
references
References 35 publications
8
119
0
5
Order By: Relevance
“…In fact, combined caudate lobe resection is considered as a standard surgical procedure for these diseases in Japan. Japanese high volume centers in which combined caudate lobe resection is routinely performed report relatively high curative resection rate (59-87%) and 5 year survival rate (33-44%) [74,87,124,127,[142][143][144][145][146][147][148]. Several reports from other countries also showed the benefits of this procedure for hilar/upper bile duct carcinoma [149][150][151][152][153][154].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, combined caudate lobe resection is considered as a standard surgical procedure for these diseases in Japan. Japanese high volume centers in which combined caudate lobe resection is routinely performed report relatively high curative resection rate (59-87%) and 5 year survival rate (33-44%) [74,87,124,127,[142][143][144][145][146][147][148]. Several reports from other countries also showed the benefits of this procedure for hilar/upper bile duct carcinoma [149][150][151][152][153][154].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…In many studies, the prognosis of patients who received combined PVR is poorer than that of patients who undergo surgical resection without PVR. However, the majority of these studies also show the prognosis of patients treated with combined PVR is significantly longer than the prognosis of unresected patients, especially in patients with hilar/upper bile duct carcinoma [71,72,74,116,155,156]. According to these reports, PVR is a safe procedure and may contribute to longer survival for patients with biliary tract cancers invading portal vein, although there is no prospective study for estimating the benefit of PVR.…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…Despite recent progress in surgical management, recurrence occurs in the majority of cases of advanced cholangiocarcinoma even after aggressive surgery [7,8]. Therefore, adjuvant chemotherapeutic treatment in addition to surgery is necessary to improve patient survival [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is a great difference in the portion of patients with Bismuth type IV, ranging from 0% to >40%. [39][40][41][42][43][44][45][46][47][48] Thus, the reported survival data needs to be interpreted carefully. The Nagoya group has recently reported that 73 patients who underwent resection for Bismuth type IV tumor and/or combined vascular resection, therefore fulfilling the "unresectability criteria" defined by the Mayo group, had a 60.4% survival rate at 5 y, similar to the survival of LT recipients.…”
Section: -31mentioning
confidence: 99%